2012
DOI: 10.1371/journal.pone.0038212
|View full text |Cite
|
Sign up to set email alerts
|

Mdm2 RING Mutation Enhances p53 Transcriptional Activity and p53-p300 Interaction

Abstract: The p53 transcription factor and tumor suppressor is regulated primarily by the E3 ubiquitin ligase Mdm2, which ubiquitinates p53 to target it for proteasomal degradation. Aside from its ubiquitin ligase function, Mdm2 has been believed to be capable of suppressing p53's transcriptional activity by binding with and masking the transactivation domain of p53. The ability of Mdm2 to restrain p53 activity by binding alone, without ubiquitination, was challenged by a 2007 study using a knockin mouse harboring a sin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 26 publications
1
10
0
Order By: Relevance
“…These findings provide an insight into why inhibition of both SirT1 and SirT2 seems to be required to achieve effective p53 activation with small-molecule sirtuin inhibitors (25). Finally, our observations are in line with previously suggested tumor suppressor roles for mdm2 (26), and the recently described positive effect of mdm2 on p53-dependent transcription when the E3 ubiquitin ligase function of mdm2 is impaired (27).…”
Section: Introductionsupporting
confidence: 90%
See 1 more Smart Citation
“…These findings provide an insight into why inhibition of both SirT1 and SirT2 seems to be required to achieve effective p53 activation with small-molecule sirtuin inhibitors (25). Finally, our observations are in line with previously suggested tumor suppressor roles for mdm2 (26), and the recently described positive effect of mdm2 on p53-dependent transcription when the E3 ubiquitin ligase function of mdm2 is impaired (27).…”
Section: Introductionsupporting
confidence: 90%
“…We speculate that additional mechanisms are likely to be required to enable a positive role for mdm2 in p53-dependent transcription in our system. In a recent groundbreaking publication, Clegg and colleagues (27) obtained enhanced expression of p53 target genes in mouse embryonic fibroblasts from an mdm2-C462A knock-in mouse model. This extremely interesting observation shows that in this model system, there are mechanisms that make it possible for mdm2 to enhance p53 transcriptional activity when mdm2 E3 ubiquitin ligase function is impaired.…”
Section: Discussionmentioning
confidence: 99%
“…A study using an MDM2 RING finger (C462A) mutant knockin mouse model by the Zhang group has shown that the stability of MDM2 is in fact not regulated by autoubiquitination in vivo [140], nor it is capable of blocking p53 activity by binding alone. This finding suggests that the MDM2 RING finger E3 ubiquitin ligase function plays an important role in suppressing p53, although this mutant is also defective in binding to MDMX [141, 142].…”
Section: Discussionmentioning
confidence: 99%
“…The MCF-7 human breast cancer and U2OS human osteosarcoma cell lines were obtained from the American Type Culture Collection (ATCC; Manassas, VA, USA). Primary MEF were prepared as previously described (37). The cells were cultured in Dulbecco's modified Eagle's medium (DMEM) (Sigma Chemical Co., St. Louis, MO, USA) or in DMEM without glucose (Gibco-Life Technologies, Grand Island, NY, USA) supplemented with 10% fetal bovine serum at 37˚C in a humidified atmosphere of 95% air and 5% CO 2 .…”
Section: Methodsmentioning
confidence: 99%